A CLINICAL STUDY OF CHANGES IN THERAPY FOR GASTROESOPHAGEAL VARICES AND ITS CLINICAL EVALUATION - MIKAMI, Yuichiro; YOSHIOKA, Takashi; MAKING, Yasuhiro; YAMASAKI, Hiroko; YUNOKI, Yasuhiro; YOSHIOKA, Toshifumi; YASUI, Masayoshi; KAWASHIMA, Takeshi; TAKEUCHI, Hitoshi; KONAGA, Eiji; TANAKAYA, Kouji; FUKAZAWA, Takuya; et al. (Japanese Journal of National Medical Services, 1995)
Two hundred and twelve patients with cardioesophageal varices were treated in Iwakuni National Hospital from January 1972 to December 1991. These patients were analyzed according to the treatment (operation, endoscopic injection sclerotherapy; EIS, EIS and operation). EIS cases have increased in the 1980s. Nowadays, about 90% of patients were treated with this method. Surgical treatment was chosen to the patients of cardial varices or secondary hypersplenism due to idiopathic portal hypertension. Prognosis was best in the patients with EIS and operation (p<0.05). There was no significant difference in prognosis between the patients with operation and those with EIS. However, prognosis of EIS was better in Child C or emergent patients. In patients with operation, liver failure was a main cause of death. On the other hand, in patients with EIS, rebleeding from varices was a main cause of death especially in the late period. From these observations, combination of operation and EIS is the most useful therapy to get a long survival time. However, transection of esophagus is difficult because of its fibrous change after EIS. We devised a new method to solve this problem. In our method, transection was carried out in the lower portion two to three centimeters below the esophagogastric junction with EEA-31® (US Auto Suture, Norwalk, Connecticut, USA) instead of the lower esophagus with EEA-25® or EEA-28®. Nonsurgical intervention for cardial varices and hypersplenism is remained to be established.